2009
DOI: 10.1016/s1472-6483(10)60052-1
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of male germ cell-like lineage from human fetal bone marrow stem cells

Abstract: Mesenchymal stem cells derived from bone marrow are a well characterized population of adult stem cells that can be maintained and propagated in culture for a long time with the capacity to form a variety of cell types. Reports have shown that murine and human embryonic stem cells can differentiate into primordial germ cells and then to early gametes. Evidence has indicated that some adult stem cells also have the potential to differentiate into germ cells. Currently, there are no reports on directed different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 27 publications
6
73
1
1
Order By: Relevance
“…Compared with our former results in mammals, the range of stem cell-specific marker-positive cells in BMCs was 11-50%, depending on the age and species of the individuals [10,27]. Previous studies have demonstrated that BMCs are capable of differentiating into various types of cells by RA in rodents and humans [10,11], along with a host of other functions, such as the regulation of development and the induction of differentiation into neural and cardiac cells [28]. However, the relevant mechanism and appropriate concentrations of RA for induction of differentiation remain to be clearly elucidated.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Compared with our former results in mammals, the range of stem cell-specific marker-positive cells in BMCs was 11-50%, depending on the age and species of the individuals [10,27]. Previous studies have demonstrated that BMCs are capable of differentiating into various types of cells by RA in rodents and humans [10,11], along with a host of other functions, such as the regulation of development and the induction of differentiation into neural and cardiac cells [28]. However, the relevant mechanism and appropriate concentrations of RA for induction of differentiation remain to be clearly elucidated.…”
Section: Discussioncontrasting
confidence: 56%
“…Recently, bone marrow (BM)-derived stem cells have been shown to transdifferentiate into multilineage cells, such as muscles of the mesoderm, the lung and liver of the endoderm and pigment cells of ectoderm origin, as well as germ cells [8][9][10][11]. Thus, the plasticity and self-renewal capacity of BMCs offer enormous potential for clinical tissue regeneration [12], and some clinical trials using MSCs in BMCs have yielded encouraging results, such as a possible cure for Parkinson's disease [13] and the regeneration of cartilage [14].…”
mentioning
confidence: 99%
“…Within two weeks, cultured BMSCs had proliferated to reach 80-90% confluence. Therefore, the shape of the proliferation curves obtained had an inverted "S" shape ( Figure 4), based on the slow proliferation that occurred 0-2 days after inoculation, followed by a period of exponential growth over days [8][9][10][11][12][13]. Consistent with the morphology of the 12 Gy-treated cells versus control cells, the rates of cell proliferation were also found to be similar for cells from group D versus group E (Figure 4).…”
Section: Effect Of Local Irradiation On Bmscsmentioning
confidence: 99%
“…Various studies have been done on derivation of male germ cells from stem cells. Bone marrow mesenchymal stem cells (BMMSC) are a good source for derived germ cells but these derived cells do not have a potential of spontaneous differentiation (Nayernia et al, 2004;Hua et al, 2009). Therefore, inductive factors are necessary for the differentiation of these derived cells.…”
Section: Introductionmentioning
confidence: 99%